Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
See below.
Step-by-step explanation:
Party A
y = x^2 + 1
For each value of x in the table, substitute x in the equation with that value and evaluate y.
x = -2: y = (-2)^2 + 1 = 4 + 1 = 5
x = -1: y = (-1)^2 + 1 = 1 + 1 = 2
Do the same for x = 0, x = 1, x = 2
x y
-2 5
-1 2
0 1
1 2
2 5
Part B
Look at points (-2, 5) and (-1, 2). The change in x from (-2, 5) to (-1, 2) is 1. The change in y is -3.
Now let's look at two other points which have a change in x of 1. Look at points (0, 1) and (1, 2). The change in x from (0, 1) to (1, 2) is 1. The change in y is 1.
You can see that for the first two points, a change of 1 in x produces a change of -3 in y, but for the second two points, the same change of 1 in x produce a change of 1 in y. Since the same change of x does not always produce the same change in y, the function is nonlinear.
Answer: A
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.